DNA methyltransferase 3B expression is associated with poor outcome of stage I testicular seminoma - Arai, Eri (Blackwell Publishing Ltd, 2012)
AIMS: To examine in testicular seminomas the expression of DNA methyltransferase 3B (DNMT3B), which is known to be associated with early embryonic development and carcinogenesis, and to obtain a predictive marker for relapse of stage I seminomas. METHODS AND RESULTS: Immunohistochemical examination of DNMT3B was performed in 88 cases of seminoma, 35 (39.8%) of which showed widely scattered nuclear immunoreactivity for DNMT3B, and 53 (60.2%) of which were completely negative. The incidence of focal DNMT3B expression was higher in stage III seminomas (5/5, 100%) than in stage I (25/70, 35.7%) or stage II (5/13, 38.5%) seminomas (P = 0.011). In stage I seminomas there were no significant correlations between DNMT3B expression and tumour size, invasion of the rete testis, or lymphatic or vascular involvement. Six of 25 cases (24%) showing DNMT3B expression relapsed, whereas only 3/45 cases (6.7%) lacking such expression did so (P = 0.037). Patients with seminomas showing DNMT3B expression had a significantly lower relapse-free survival rate than patients whose tumours lacked this feature (P = 0.0464). CONCLUSIONS: Patients with seminomas showing focal DNMT3B expression are at increased risk of relapse, and should be followed up carefully.